Lignocellulosic fiber media filters as a potential technology for primary industrial wastewater treatment - Mohd Nawawi, Mohd Ghazali; Othman, Norasikin; Sadikin, Aziatul Niza; Che Ismail, Norhafizah (Penerbit UTM Press, 2008)
By-products from palm oil mill constitute the most abundant renewable resources available in Malaysia. Among these by-products, empty fruit bunches constitutes a significant portion of mill residues. The abundance of oil palm empty fruit bunches has created a vital environmental issue. Thus, the use of the lignocellulosic fibers would add its economic value, help reduce the cost of waste disposal, and most importantly, provide a potential inexpensive alternative to existing pre-treatment of palm oil mill effluent. This study was carried out to investigate the potential application of empty fruit bunches as a fiber filter media to remove oil and grease, turbidity and organics in term of Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) from palm oil mill effluent treatment process. Oil palm empty fruit bunch (OPEFB) fibers were modified with chitosan solution before processed into a mat-type filter medium. Microscope images revealed surface morphology changes of the fibers due to the chemical treatment. Benchscaled experiment results indicated that pre-treatment using the fiber filtration system removed up to 66% of turbidity, 67% of Total Suspended Solid (TSS) and 85% of oil and grease. The results show that the lignocellulosic fiber filter could be a potential technology for primary wastewater treatment.